Proceedings of the 6th ACM International Symposium on Pervasive Displays 2017
DOI: 10.1145/3078810.3078830
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for multi-stakeholder display analytics

Abstract: Measuring viewer interactions through detailed analytics will be crucial to improving the overall performance of future open display networks. However, in contrast to traditional sign and web analytics systems, such display networks are likely to feature multiple stakeholders each with the ability to collect a subset of the required analytics information. Combining analytics data from multiple stakeholders could lead to new insights, but stakeholders may have limited willingness to share information due to pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…While traditional display networks have operated as largely closed systems (managed by a single organisation), there has been increasing interest in stimulating innovation by creating "open display networks" that can accommodate content and control from multiple sources [26]. Such networks are characterised by open APIs and software components that enable developers to create new signage applications [26,83], techniques for enabling content ingestion from multiple sources [21], and recognition of the complex set of stakeholders that exist in such networks [4,21,63,89]. In [26] the authors provide three example scenarios of potential applications for open display networks:…”
Section: Openness and Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…While traditional display networks have operated as largely closed systems (managed by a single organisation), there has been increasing interest in stimulating innovation by creating "open display networks" that can accommodate content and control from multiple sources [26]. Such networks are characterised by open APIs and software components that enable developers to create new signage applications [26,83], techniques for enabling content ingestion from multiple sources [21], and recognition of the complex set of stakeholders that exist in such networks [4,21,63,89]. In [26] the authors provide three example scenarios of potential applications for open display networks:…”
Section: Openness and Controlmentioning
confidence: 99%
“…The problem is compounded by the diverse set of stakeholders involved. Prior research has identified four stakeholders in typical public display deployments: display owners, space owners, content providers, and viewers [4,21,63,89]. In traditional display systems many of these stakeholders are represented by a single organisation (e.g.…”
Section: Openness and Controlmentioning
confidence: 99%
See 1 more Smart Citation